The Uses of Social Media in Journalism Practices: The Reversed-Agenda Setting on Television News Production - Bintan Humeira; Andika Ramadhan (Jurnal Studi Jurnalistik, 2022)
This article aims to examine the use of social media by television journalists in Indonesia (Kompas TV) in the broadcast production process and the implications for changing the influence of the media on the public agenda. This research uses an agenda-setting perspective in the internet era and an in-depth interview method with senior journalists and broadcast producers. The results show that using social by journalists includes pre-production to post-production activities. From the type of information source, journalists often use four social media accounts: social media accounts belonging to influencers, community leaders (politicians, observers, or academics), institutions, and communities. This study also shows that conversations on social media are a means for the press to find issues of public concern and ultimately affect news content. Furthermore, this study supports the concept of a reversed-agenda setting in that the media is no longer dominant in determining the public agenda. On the other hand, the public has the power to decide on their agenda, not depending on the media. Public opinion often influences media coverage. Moreover, the logic of the digital space that emphasizes user engagement as a measure of popularity makes taking sides with the public important to increase digital traffic and has the potential to provide economic benefits. In addition, this research also finds that journalists often access social media accounts belonging to mainstream media as a source of information rather than visiting news sites owned by the media. It shows that social media allows for a more significant intermedia agenda-setting effect.